Nurses' Moral Sensitivity and Hospital Ethical Climate: a Literature Review - Schluter, Jessica (Nursing ethics, 2008)
Increased technological and pharmacological interventions in patient care when patient outcomes are uncertain have been linked to the escalation in moral and ethical dilemmas experienced by health care providers in acute care settings. Health care research has shown that facilities that are able to attract and retain nursing staff in a competitive environment and provide high quality care have the capacity for nurses to process and resolve moral and ethical dilemmas. This article reports on the findings of a systematic review of the empirical literature (1980 — February 2007) on the effects of unresolved moral distress and poor ethical climate on nurse turnover. Articles were sought to answer the review question: Does unresolved moral distress and a poor organizational ethical climate increase nurse turnover? Nine articles met the criteria of the review process. Although the prevailing sentiment was that poor ethical climate and moral distress caused staff turnover, definitive answers to the review question remain elusive because there are limited data that confidently support this statement.